Opinion of the Farmers towards Different Methods of Paddy Cultivation During Covid-19 - Singla, Sahil; Kaur, Kamalpreet (International Journal of Economic Plants, 2023)
The study was conducted in five agro-climatic zones of Punjab in 2020–21 during COVID-19. From a sample of 150 respondents, about 45% had average opinion regarding the conventional transplanting, mechanical transplanting and direct seeded paddy methods of sowing. All the respondents were agreed that direct seeded paddy is more water saving technology. For good yield, rank first was given to mechanical transplanting and rank third was given to direct seeded paddy methods of sowing. The data revealed that majority of respondents agreed with the statement that intercultural operations was easy in mechanical transplanting. Majority of the respondent disagreed with the statement of better weed control in DSR. Greater majority of respondents agreed with the statement that in conventional transplanting, transplanting is easy. About eighty six per cent of respondents disagreed with statement that growing nursery was easy in mechanical transplanting. All the respondents disagreed with the statement of water saving in conventional transplanting. Greater majority of respondents disagreed that labour was easily available for conventional transplanting during Covid-19.